2017
DOI: 10.1038/s41419-017-0077-5
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-221-3p, a TWIST2 target, promotes cervical cancer metastasis by directly targeting THBS2

Abstract: MicroRNAs have implicated in the relapse and metastasis of cervical cancer, which is the leading cause of cervical cancer-related mortality. However, the underlying molecular mechanisms need further elucidation. Our present study revealed that miR-221-3p is transcriptionally promoted in metastatic cervical cancer tissues compared with non-metastatic cervical cancer tissues. Forced overexpression of miR-221-3p facilitated EMT and promoted cell migration and invasion in vitro and lymphatic metastasis in vivo. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 43 publications
(44 reference statements)
3
59
0
Order By: Relevance
“…Bioinformatics analysis ( http://starbase.sysu.edu.cn/ ) found that miR-221 was the target of GAS5. Increasing evidence has shown that miR-221 promotes carcinogenesis, including cervical cancer, 24 osteosarcoma, 20 and lung cancer. 25 We found that miR-221 was upregulated in both PC tissues and cell lines ( Figures 1 C and 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Bioinformatics analysis ( http://starbase.sysu.edu.cn/ ) found that miR-221 was the target of GAS5. Increasing evidence has shown that miR-221 promotes carcinogenesis, including cervical cancer, 24 osteosarcoma, 20 and lung cancer. 25 We found that miR-221 was upregulated in both PC tissues and cell lines ( Figures 1 C and 1D).…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNA-221/222 participates in the progression of many tumors and has been reported to be highly expressed in cervical cancer 47 50 . Besides, two studies have revealed that HMGA1 could affect the expression of miR-222 in lung cancer 41 , 51 .…”
Section: Resultsmentioning
confidence: 99%
“…The abnormal expression of miRNAs in tumors is a research hotspot in the field of oncology. A variety of miRNAs that regulate the biological behavior of cervical cells through different target genes and participate in the occurrence, invasion, and metastasis of cervical cancer have been observed to be expressed abnormally in cervical cancer [8][9][10].…”
Section: Introductionmentioning
confidence: 99%